Propeptide of a precursor to a plant vacuolar protein required for vacuolar targeting. - Matsuoka, K (1991)
Sporamin is a protein without glycans that accumulates in large quantities in the vacuoles of the tuberous root of the sweet potato. It is synthesized as a prepro precursor with an N-terminal extension composed of a 21-amino-acid signal peptide and a 16-amino-acid propeptide. A total of 48 base pairs, corresponding to the nucleotide sequence that encodes the propeptide, was deleted from a cDNA clone for sporamin. This delta pro mutant sequence, as well as the sequence of the wild-type sporamin cDNA, was placed downstream from the promoter of the 35S transcript from cauliflower mosaic virus and introduced into the genome of suspension-cultured tobacco cells by Agrobacterium-mediated transformation. In contrast to the vacuolar localization of sporamin in cells that expressed the wild-type precursor, sporamin was secreted into the culture medium from cells in which the delta pro precursor was expressed. The secreted form of sporamin was shorter by two amino acids at its N terminus than authentic sporamin; it migrated anomalously during electrophoresis on SDS/polyacrylamide gel as a result of the presence of intramolecular disulfide bridges, as does authentic sporamin. The kinetics of secretion of sporamin from the cell were similar to those of proteins normally secreted by the host tobacco cells. These results indicate that the propeptide of the precursor to sporamin is required for correct targeting of sporamin to the vacuole and that proteins can be secreted from plant cells by a bulk-flow default pathway in the absence of a functional sorting signal.